A large-scale life-cycle assessment of recycled aggregate concrete: The influence of functional unit, emissions allocation and carbon dioxide uptake. (1st March 2020) - Visintin, P.; Xie, T.; Bennett, B.
Abstract: In an attempt to limit the environmental impact of cement and concrete manufacture, much research has been devoted to the potential use of concrete waste as recycled aggregate. While this research has shown technical feasibility, a limited amount of research has been devoted to quantifying the environmental impact of recycled aggregate concrete production. In this work, to quantify the CO2 equivalent emissions and embodied energy of a broad range of mixes, life-cycle assessment is undertaken on 624 recycled aggregate concrete mix designs collated from 61 individual studies. The study includes: consideration of an expanded functional unit that accounts for the potential need to increase cement content to allow for the loss of strength and durability associated with recycled aggregate inclusion, the impact of the allocation of emissions from the recycling process, and the uptake of CO2 during the primary and secondary life as a result of carbonation. Based on the large-scale life-cycle assessment, emission factors for recycled aggregate concrete are defined, and it is shown that considering an expanded functional unit incorporating volume, strength and durability yields similar mean emission factors to a simple volumetric functional unit but with a significantly larger range. Further it is shown that due to the high carbonation rate, in many instances the crushing of concrete to aggregate size and use as fill may be preferable in comparison to use in concrete.